Genetics of neuroendocrine prostate cancer: recent progress in genetic understanding is translating into therapeutic opportunities. Issue 5 (15th September 2022) - Rinott Mizrahi, Gal; Williams, Isabella; Azad, Arun; Lawrentschuk, Nathan
Abstract : Purpose of review: Neuroendocrine prostate cancer (NEPC) is a rare histologic subtype of prostate cancer with extremely aggressive clinical behaviour and very limited data regarding treatment options. This review is intended to relay new research advances in the understanding of the genetic and epigenetic aberrations underlying NEPC development and to review new targeted therapeutic options developed based on NEPC genetics. Recent findings: Multiple genomic alterations and epigenetic regulators have been identified in NEPC development. Among these are amplifications of oncogenic transcriptional factors, changes in expression of cell surface markers and epigenetic alterations. This in turn has facilitated a number of new targeted therapies for NEPC that act via different mechanisms including catalytic inhibitors, immune-modulators and epigenetic modifiers. These targeted therapies are now being studied in different phases of clinical trials with some preliminary results showing efficacy. Summary: NEPC is a highly aggressive malignancy with currently lack of effective treatments. Considerable challenges still remains to improve clinical outcomes in NEPC; however, ongoing trials exploiting novel genetic and epigenetic alterations hold promise for patients suffering from this aggressive disease.